A Highly Efficient Copper-Catalyzed Synthesis of Unsymmetrical Diaryl- and Aryl Alkyl Chalcogenides from Aryl Iodides and Diorganyl Disulfides and Diselenides - Movassagh, Barahman; Hosseinzadeh, Zhila (Synlett, 2016)
An efficient and convenient protocol has been developed for the copper-catalyzed reaction of aryl iodides and diorganyl disulfides and diselenides. A variety of symmetrical and unsymmetrical diaryl- and aryl alkyl chalcogenides were synthesized with good functional group tolerance and chemoselectivity by using copper(Ι) iodide as a catalyst, 4′-(4-methoxyphenyl)-2,2′:6′,2′′-terpyridine as ligand, and KOH as base under an inert atmosphere.
Keywords: cross-coupling; diaryl chalcogenides; copper-catalyzed reaction; aryl halides; dichalcogenides